If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-2)-3(x+1=4(3+2)
We move all terms to the left:
6(x-2)-3(x+1-(4(3+2))=0
We add all the numbers together, and all the variables
6(x-2)-3(x+1-(45)=0
We add all the numbers together, and all the variables
6(x-2)-3(x+1-45=0
We multiply parentheses
6x-3(x+1-45-12=0
| 3(x+4)=(4x-9) | | 2(y+6)=22−3y | | 75=(2x+15) | | -15.7=w/5-3.2 | | 28=4(7)+4y | | 8x-4+7x+3=360 | | 30=2/5÷x | | 30=x÷2/5 | | 30=x+2/5 | | (x+8)(8x+1)=90 | | -15+2x=10-3x | | 3x+5x+17=64 | | 4(x-12)=-28 | | (24+x)+x+2x=124 | | (2x-3)+(2x-3)+x=34 | | -1.1x–4=0.8 | | M=-4,b=8/5 | | -8x+10=-6x+6= | | M=-2,b=4/3 | | 24+x+2x=124 | | 14d−12d=10 | | 3x2+4x2÷2x+9=5 | | 11x-5+4x=-22+10x-3 | | 4(2a+3)=3(a-1)+31= | | 2x+14-6x-3=-9 | | -3(4x-2)-2=x | | 0.25x=11.25 | | 52-2p=10+2p | | 4y2=-100 | | 8x-5+8x-5+4x-7+4x-7=360 | | 16^x^2=8^0 | | 8x+1=7x-10 |